"Reflective of my best work": Promoting inquiry-based learning in a hybrid graduate history course. (July 2020) - Sleeter, Nate; Schrum, Kelly; Swan, Amy; Broubalow, Justin
Abstract: This article discusses authentic inquiry-based learning in a hybrid graduate course, Teaching Hidden History, taught in 2015 and 2016. Students in this course created online history learning modules based on their own scholarly research. They defined their intended audience and crafted modules tailored specifically for those learners. The authors draw on course assignments, student modules, interviews, and focus group data to present a model of how inquiry-based learning can be scaffolded to promote the benefits of student-centered inquiry – namely the intrinsic motivation associated with the creation of authentic projects and practical skill acquisition.